A Quasi-periodic Propagating Wave and Extreme-ultraviolet Waves Excited Simultaneously in a Solar Eruption Event - Miao, Yu Hu; Liu, Yu; Shen, Yuan Deng; Li, Hong Bo; Abidin, Zamri Zainal; Elmhamdi, Abouazza; Kordi, Ayman S. (IOP Publishing, 2019)
Quasi-periodic fast-propagating (QFP) magnetosonic waves and extreme-ultraviolet (EUV) waves were proposed to be driven by solar flares and coronal mass ejections (CMEs), respectively. In this Letter, we present a detailed analysis of an interesting event in which we find that both QFP magnetosonic waves and EUV waves are excited simultaneously in one solar eruption event. The co-existence of the two wave phenomena offers an excellent opportunity to explore their driving mechanisms. The QFP waves propagate in a funnel-like loop system with a speed of 682-837 km s -1 and a lifetime of 2 minutes. On the contrary, the EUV waves, which present a faster component and a slower component, propagate in a wide angular extent, experiencing reflection and refraction across a magnetic quasi-separatrix layer. The faster component of the EUV waves travels with a speed of 412-1287 km s -1 , whereas the slower component travels with a speed of 246-390 km s -1 . The lifetime of the EUV waves is ∼15 minutes. It is revealed that the faster component of the EUV waves is cospatial with the first wavefront of the QFP wave train. The QFP waves have a period of about 45±5 s, which is absent in the associated flares. All of these results imply that QFP waves can also be excited by mass ejections, including CMEs or jets. © 2019. The American Astronomical Society. All rights reserved.